(untitled) (Global Journal of Science Frontier Research, 2022)
The very rapid growth in the need for communication, both quantitatively in terms of telephone links and in terms of quality as a result of the diversification of new services related to the introduction of digital technology, is making it necessary again to design a new system. Optical fiber transmission is becoming more and more common in modern society. The optical fiber has the property of driving light and serves in terrestrial and oceanic data transmissions, as well as in medical or industrial imaging applications. Today, data transfer must provide extreme performance. This requirement can only be fulfilled with perfect optical fibers, integrated in fiber optic cables of irreproachable quality.